2021
DOI: 10.31550/1727-2378-2021-20-2-11-20
|View full text |Cite
|
Sign up to set email alerts
|

Management of Patients with Diabetes Mellitus and COVID-19

Abstract: Objective of the Review: To systematise the information on the incidence of diabetes mellitus (DM) in patients who had the novel coronavirus infection; on the features of virus mechanism activation and pathological cascades in the body; on potential ways to control blood glucose during COVID-19. Key Points. During the novel coronavirus pandemic (COVID-19) associated with high death toll in all countries, specific groups of patients were identified, where the death rate was higher than the mean figures. These g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…To stratify the risk of in-hospital death depending on the severity of type 2 diabetes, patients with T2D were divided into two subgroups depending on blood glucose level upon admission to COVD-19-hospital with a cutoff 10 mmol/L, according to the studies of Zhu L. et al (2020) and Andreeva A.V. et al (2021) [1,16]. These previous researchers found that well-controlled blood glucose ranging from 3.9 to 10.0 mmol/L is associated with a significant reduction in composite adverse outcomes and death [1,16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To stratify the risk of in-hospital death depending on the severity of type 2 diabetes, patients with T2D were divided into two subgroups depending on blood glucose level upon admission to COVD-19-hospital with a cutoff 10 mmol/L, according to the studies of Zhu L. et al (2020) and Andreeva A.V. et al (2021) [1,16]. These previous researchers found that well-controlled blood glucose ranging from 3.9 to 10.0 mmol/L is associated with a significant reduction in composite adverse outcomes and death [1,16].…”
Section: Discussionmentioning
confidence: 99%
“…et al (2021) [1,16]. These previous researchers found that well-controlled blood glucose ranging from 3.9 to 10.0 mmol/L is associated with a significant reduction in composite adverse outcomes and death [1,16]. In our study, moderate T2D with glucose level <10 mmol/L had a lower hospital mortality rate than severe (p = 0.018), and both T2D groups had higher mortality than control COVID-19 patients (p = 0.033 and p < 0.001 consequently), which supports the correlation of T2D severity and hospital complication rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation